Terapi Aktivitas Kelompok Stimulasi Kognitif Dengan Menyusun Kolase Gambar Menggunakan Media Kulit Kacang Di Wisma Pisang PSTW Budi Mulia 2 - Haetami, Fajar; Safitri, Alfika; Nimastin. P. N, Cindy Ilmi; Rahayu, Suci; Carsilah; Nurohmah, Aan Juliyanti; Julianti, Alfiani Dwi; Urbaningrum, Aliza Fatma; Hanik, Ade Ummi; Suyaniaga (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction : Aging is a natural process that is often accompanied by a decline in cognitive functions in the elderly, such as memory, concentration, and thinking ability. This condition can reduce the quality of life and increase the risk of dementia. In Indonesia, the trend of increasing the number of elderly people demands interventions to maintain their cognitive function. Group Activity Therapy (TAK) is one of the effective approaches to stimulate cognition and improve social interaction among the elderly. This activity aims to stimulate cognition, train fine motor skills, and increase social interaction in a fun and meaningful way. Objective: The purpose of group activity therapy (TAK) Compiling Image Collages using peanut peel media is expected to increase cognitive stimulation and increase social interaction in the elderly at the Tresna Werdha Budi Mulia 2 Social Home. Method: This group activity therapy is divided into 4 stages, namely, the preparation stage, the administration of group activity therapy (TAK), the implementation of TAK and final reporting. Instrumen yang digunakan untuk mengukur fungsi kognitif pada lansia adalah alat ukur MMSE (Mini Mental Scale Examination) , dan instrumen untuk mengukur tingkat interaksi sosial menggunakan kuesioner interaksi sosial Result: Based on the results of this observation, it can be concluded that group activity therapy activities run effectively and have a positive impact on increasing the interest, enthusiasm, and cognitive function of elderly participants. This activity also improves social interaction and the mood of participants Conclusion: The results of this activity are relevant to the research of Dewi (2023) who stated that the application of Group Activity Therapy (TAK) with the therapy of compiling image collages using pat peanut peel media improves cognitive function in the elderly.